Development of History Learning Media Using Documentary Videos with the Subtheme of the Battle of Palagan Ambarawa in Class XI of SMA N 1 Ambarawa - Pradana, Angga; Pramono, Suwito Eko; Atno, Atno (Indonesian Journal of History Education, 2020)
This study aims to know and analyze the feasibility of developing historical learning media with the Battle of Palagan Ambarawa subteam to the needs of students in class XI SMA N 1 Ambarawa. The method used in this research is Research and Development. The data sources in this study are teachers, students, the learning process, documents, and questionnaires. Data objectivity tests used are triangulation method, source triangulation, and validity. The data analysis technique in this research is qualitative descriptive for the preliminary, quantitative analysis technique for the development stage. The evaluation stage uses the Likert scale quantitative analysis technique. The feasibility level from the media experts showed an average of 82.78% (rated as an outstanding category), and material experts averaged 87.5% (rated as an exceptional category). Class XI IPS I got a response rate of 87.2% (outstanding category), and class XI MIPA IV got a response rate of 81.6% (rated as a good category).